Mozart's Viennese instrumental music : a study of stylistic re-invention - Keefe, Simon P., 1968- (Boydell, 2007)
The stylistic evolution of Mozart's Viennese instrumental repertory as a whole [1781-1791], closely tied to historical and contextual lines of inquiry, has yet to receive systematic attention. This book fills the gap through a study of stylistic re-invention, a practically- and empirically-based theory that explains how innovative, putatively inspired ideas take shape in Mozart's works and lead to stylistic re-formulation. Re-invention comprises a two-stage process: Mozart manipulates pre-existent stylistic features of his music to climactic effect, in so doing introducing a demonstrably 'new' stylistic dimension with broad aesthetic resonance; he subsequently re-appraises his style in response to the dimension in question. From close examination of a variety of Mozart's works [piano concertos, string quartets and symphonies in particular], supported by study of Mozart's other chamber and dramatic works, the author shows that stylistic re-invention is a consistent and coherent manifestation of stylistic development. Ultimately re-invention puts center stage the interaction of intellectual and imaginative elements of Mozart's musical personality, accounting both for process of reflection and re-appraisal and for striking conceptual leaps.